Survival and early growth of acacia mangium, ceiba pentandra and casuarina equisetifolia on sandy tin tailings - Nik Ab. Majid, Nik Muhamad; Paudyal, Bimal Keshari; Shebli, Zarina (Universiti Putra Malaysia Press, 1998)
A field study was carried out on tin tailings to evaluate the growth performance of three timber species (Acacia mangium, Ceiba pentandra and Casuarina equisetifolia) with and without fertilization and with three species of cover crops (Centrosema pubescens, Calopogonium muconoides and Puereria phaseoloides). The experiment was carried out at Kampung Pasir, Semenyih, Ulu Langat, Selangor. NPK compound fertilizer was applied at the mle of 300 g per seedling ever)' three 'months during the first year of the study. Height and diameter were measured 23 months after planting. Soil samples were also collected for laborator), analysis. The results showed that the three timber species can grow well even without fertilizer and the growth -rates of the three species differ significantly. The fastest growth rate was recorded by Acacia mangium followed by Ceiba pentandra and Casuarina equisetifolia. The planting of cover crops slightly increased the nuttient status of the soil. Thus this experiment shows that timber species, particularly Acacia mangium, could be successfully used to rehabilitate abandoned examining land, while Ceiba pentandra and Casuarina equisetifolia could also be used, but have slower growth -rates than Acacia mangium.